2011
DOI: 10.1504/ijgw.2011.044393
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of vehicle fuel-type preference in developing countries: a case of Turkey

Abstract: Motor vehicles play a major role in global warming. The main contribution of motor vehicles comes from the emission of carbon dioxide (CO 2 ). This study aims to identify the factors affecting the preferences for vehicle fuel types in Turkey. To meet this objective, a survey was conducted with 1983 participants in different regions of Turkey by the DataProfil survey firm. Results obtained from a multinomial logit model show that variables such as gender, attitudes towards alternative energy sources, social res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Studies developed in North America [5,6,16,26,37,44,83,87] and Europe [21,23,46,77,78,95] reported that younger consumers are more willing to buy greener vehicles (with the exception of [53]). On the other hand, Asian studies, with the exception of [58], found that older consumers have higher propensity to buy AFVs [19,59,61,88]. Therefore, the summarized results are consistent with hypothesis H2.…”
Section: Age Influencesupporting
confidence: 80%
See 4 more Smart Citations
“…Studies developed in North America [5,6,16,26,37,44,83,87] and Europe [21,23,46,77,78,95] reported that younger consumers are more willing to buy greener vehicles (with the exception of [53]). On the other hand, Asian studies, with the exception of [58], found that older consumers have higher propensity to buy AFVs [19,59,61,88]. Therefore, the summarized results are consistent with hypothesis H2.…”
Section: Age Influencesupporting
confidence: 80%
“…Qian and Soopramanien [58] average distance from home to workplace, no. of working members Senturk et al [59] [61] no. family members with driver license Achtnicht et al [20] Hess et al [48] house location, no.…”
Section: Vehicle Attributes Interactionmentioning
confidence: 99%
See 3 more Smart Citations